Lesbian, gay, bisexual, transgender, intersex, and its legalisation in Africa: Insights from tertiary-level students in Ghana. - Francis Acquah; Charles Owusu-Aduomi Botchwey; Prince Owusu Adoma; Emmanuel Kumah (PLoS ONE)
Introduction Lesbian, gay, bisexual, transgender, and intersex (LGBTI) and related activities have been a topic of debate and discussion among policymakers and stakeholders, as well as common citizens in the African region, especially in Ghana. The current anti-LGBTI-related bill being put before Ghana's Parliament signifies the intensity of the issue. Even though some studies have looked at some aspects of the issue, no study presently has explored people's opinion on the passage of any future anti-LGBTI and related legislations in Ghana. Aim This study examined the perspective of tertiary-level students on the passage of anti-LGBTI legislation, as well as the non-physical factors that influence support for the passage of anti-LGBTI and related legislation in Ghana. Methods The study employed a quantitative cross-sectional design using 1,001 tertiary-level students. The study used convenience sampling technique with an online closed-ended, structured survey questionnaire as the main data collection instrument. The data was then analysed using Statistical Package for the Social Sciences, version 29 at a 5% significance level. Results The results of the study indicated that majority of the respondents (81%) were in support of the passage of anti-LGBTI and related legislations. Their reasons included the health implications of LGBTI and related activities (63%), cultural and societal values (62%), religious reasons (54%), and western culture (25%). Also, almost half of the respondents (49%) held that health related perceptions about LGBTI have little or no empirical basis. The inferential analysis, further, revealed that even when age and sex assigned at birth are controlled, perceived health implications of LGBTI (β = 0.247, p = < .001), religious beliefs (β = 0.189, p = < .001), and cultural values (β = 0.218, p = < .001) positively predict the support for passage of anti-LGBTI legislation. Conclusions People's level of support for the passage of anti-LGBTI legislation is influenced by several factors including religious beliefs, cultural values, and the perceived health implications of LGBTI. There is, however, the need for policy makers and other stakeholders to create awareness and educate the public about the various perceptions about LGBTI and related activities that are not scientifically legitimate.